Europium-Doped Ceria Nanowires as Anode for Solid Oxide Fuel Cells - Li, Shuai; Lu, Xia; Shi, Siqi; Chen, Liquan; Wang, Zhaoxiang; Zhao, Yusheng (Frontiers in Chemistry, 2020)
CeO2-based materials have been studied intensively as anode for intermediate temperature solid oxide fuel cells (IT-SOFCs). In this work, pristine and europium (Eu)-doped CeO2 nanowires were comprehensively investigated as anode materials for IT-SOFCs, by combination of theoretical predictions and experimental characterizations. The results demonstrate: (1) Oxygen vacancy can be energetically favorably introduced into the CeO2 lattice by Eu doping; (2) The lattice parameter of the ceria increases linearly with the Eu content when it varies from 0 to 35 mol.%, simultaneously resulting in the significant increase of oxygen vacancy. The content of oxygen vacancy reaches its maximum at ca. 10 mol.% Eu doping level and decreases thereafter; (3) The highest oxygen ion conductivity is achieved at a Eu content of 15 mol.%; while the 10 mol.% Eu-doped CeO2 sample displays the highest catalytic activity for H2-TPR and CO oxidization reactions. The conducting and catalytic properties are beneficial from the expanded lattice, the large amount of oxygen vacancies, the enhanced reactivity of surface oxygen and the promoted mobility of bulk oxygen ions. These results provide a rewarding avenue towards designing and optimizing CeO2 as a promising anode for SOFCs.